Analisis Strategi pada Mrs Brew Kitchen Terhadap Penjualan - Glaudius Galenus; Hariyadi B. Sukamdani; Bernard Hasibuan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Mrs. Brew Kitchen is a company operating in the food industry, specifically a café with a theme of mini kitchen. This company started its operations at the end of 2022 with several drink and snack menus. Until now, the company has various types of menus starting from coffee drinks to heavy meals. Because it is in a strategic location, several entrepreneurs also have the same thoughts about building the same type of business so there are many competitors. As a new company, a good strategy is crucial to get customers and increase sales. The aim of the research is to determine the company's position in order to design the right strategy using the IFAS, EFAS and IE matrixes, obtain several alternatives from the company's internal and external factors using the SWOT Matrix, and sort alternative strategies based on the most important order using the QSPM method. The company's position in Cell I indicates that the company can use intensive and integration strategies, but apart from implementing intensive marketing strategies, the company prioritizes strategies to maintain consistency first.